REDUPLIKASI DALAM BUKU TEKS MATA PELAJARAN BAHASA INDONESIA KELAS IX E KARANGAN AGUS TRIANTO, TITIK HARSIATI, E. KOSASIH TAHUN 2018 - Ade Rahima; Dini Rantiwi (Universitas Batanghari, 2022)
This study aims to describe the form and meaning of reduplication in Indonesian subject textbooks of class IX by Agus Trianto, Titik Harsiati, and E. Kosasih in 2018. This type of research includes qualitative descriptive research, the data contained in this study is in the form of sentences containing the form and meaning of duplication. The source of the data that will be in the study is Indonesia subject textbook of class IX by Agus Trianto, Titik Harsiati, and E. Kosasih in 2018 in the form of sentences. The collection technique in this study used documentation techniques. In this study, the author analyzed the data using structural theory from Sugiyono. Based on the results of the research conducted, findings were obtained, namely the form of reduplication and the meaning of reduplication. From the findings, it was concluded that the form of reduplication found was 202 citations consisting of (1) a complete reduplication of 147 citations, including: people, (2) reduplication of vote copy as many as 4 citations, including: colorful, (3) partial reduplication of 32 citations, including: looking around and (4) reduplication of philosophizing as many as 19 citations, including: as many as possible. Meanwhile, the meaning of reduplication found as many as 201 citations consisting of (1) the meaning of transitive derivative duplication of 35 citations, including: continuously, (2) the meaning of the duplication of nontransitive derivatives as many as 21 citations, including: looking around, (3) the meaning of duplication of adjective derivatives as many as 23 citations, including: wide and (4) meanings of duplication of nomina derivatives as many as 120 quotations, among others: checkered. From the results of the duplication form research, the most findings were found in intact duplication while in the study the meaning of the most reduplication was found in the meaning of the reduplication of the noun derivative.